KOMPOSISI ASET DAN AKTIVITAS TERHADAP FRAUD LAPORAN KEUANGAN - Nelsen, Nelsen; Tjahjono, Rudi Setiadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Research of Fraudulent Financial Reporting is to obtain empirical evidence about the influence of financial ratio especially for asset composition, activity, profitability, liquidity, leverage, capital turnover, and other factors such as: managerial ownership, and firm size on fraudulent financial reporting. Research population of this research are non financial firms that listed in Indonesia Stock Exchange at 2016 until 2019. There are 169 companies selected as a samples by using purposive sampling method. Sample of this research are analyzed and tested using logistic regression method. Result of this research implies that profitability, liquidity, leverage, and managerial ownership have no significanct influence toward fraudulent financial reporting, but asset composisition and activity have positive influence on fraudulent financial reporting, and then capital turnover and firm size have negative influence toward the occurrence of fraudulent financial reporting.